MODEL OF DA'WAH AND MOSQUE-BASED EDUCATION CASE STUDY OF REVIEWING CHILDREN WALADUN SHOLIH MASJID AL-FURQAN OF DEWAN DA'WAH - Abdul Kadir (Jurnal Da'wah: Risalah Merintis, Da'wah Melanjutkan, 2022)
Research purposes:This study aims to uncoverthe model of education and coaching carried out by the Waladun Sholih Children's Study at the al-Furqan mosque of the Indonesian Islamic Da'wah Council. Research Methods: Qualitative. Research result:Two models of education conducted by PA. Waladun Sholih. The first model isthe children registered by their parents are then intensively trained and directed to the correct understanding and practice of Islam, in accordance with the Qur'an and as-Sunnah. At this stage, the trust of parents/guardians in what we do is the most important capital. So, of course, a well-organized work system is needed, starting from the provision of educators, compiling the curriculum and schedule to procuring the facilities. The second model is by activating the participation of parents of students to take quarterly monthly general recitations at the Al-Furqan Mosque as well as to follow reports on their children's educational progress. There are four targets that Pengjian Waladun Sholih wants to carry out in improving the quality of education and achieving educational targets. The four things include; First; Adjustment of Materials and Methods of Delivery to the level of student acceptance, which includes aspects of Reason, Appreciation and Skills. Second; Curriculum Improvement and Addition of Subject Matter. Third; Distribution of Report Values ​​according to the observed Educational aspects. It is deemed very necessary for educators, students and parents/guardians. Fourth: Improving the structure of education levels and the period of each level.